Enlargements and the Principles of Designing EU - Decision-Making Procedures - Mika Widgrén (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper examines how neutral the current EU decision-making procedures are to membership and how well they obey certain transparent general constitutional principles. The paper evaluates the performance of the procedures by strategic and classical power indices. The main emphasis in the assessment is in stability, efficiency and fairness. The paper concludes that co-decision either with shared right to initiate between the Commission and the the Parliament or a double-hat Presidency works the best. In the Council the current weighting should be replaced by the dual majority of square-rooted populations and Member States.
Keywords: 330